Pengaruh Faktor-Faktor Perilaku Konsumen Terhadap Keputusan Pembelian Mebel pada Toko Udin Surya Tanah Grogot - Achmad Syahruddin; Istiqomah Istiqomah; Biyuta Biyuta (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this research is to determine the simultaneous and partial influence as well as the dominant variables of consumer behavior consisting of culture (X1), social (X2), personal (X3), and psychological (X4) on purchasing decisions (Y) for furniture at the Udin Surya Store. The sample in this study was furniture buyers at the Udin Surya Store who met with researchers from June to July 2023 using incidental sampling techniques and the number of samples obtained was 50 people. Buyers as the sample in this study were given a questionnaire consisting of 25 statements. Responses to the questionnaire were tested for validity and reliability before multiple linear regression analysis was carried out using the SPSS application. The results of testing the research instrument, namely the questionnaire, show that the 25 statement items are valid because r count > r table. Apart from that, all statements are reliable because the Cronbach's Alpha value is > 0.60 (0.915 > 0.60). The regression equation obtained is Y = 7.308+0.015X1+0.168X2 +0.199X3+0.535 X4. The correlation coefficient value is 0.789, this shows a strong relationship between consumer behavior consisting of culture (X1), social (X2), personal (X3), and psychological (X4) on the decision to purchase (Y) furniture at the Udin Surya Store. The coefficient of determination value is 0.589, which means that consumer behavior consisting of cultural (X1), social (X2), personal (X3), and psychological (X4) on purchasing decisions (Y) for furniture at the Udin Surya Store is 58.9% while the remaining 41 .1% is influenced by factors not included in this study. Simultaneous testing shows that the value of Fcount > Ftable (18.553 > 2.58) so it can be concluded that there are consumer behavior variables consisting of cultural (X1), social (X2), personal (X3), and psychological (X4) which influence jointly on decision to purchase (Y) furniture at the Udin Surya Store. Next, a partial test was carried out by looking at the calculated t value for each sub-variable of consumer behavior consisting of culture (X1), social (X2), personal (X3), and psychological (X4), each of which was 0.052; 1,283; 1,211; 4.804 which when compared with the t table of 2.01410, then psychological (X4) is 4.804 > 2.01410, the dominant influence on purchasing decisions (Y) for furniture at the Udin Surya Store because t count > table. Meanwhile, culture (X1), social (X2), personal (X3) do not have a significant effect on purchasing decisions (Y) for furniture at the Udin Surya Store because the calculated t value < t table.